Study on Organic Modification of Lanthanum Oxide. Issue 1 (1st February 2022) - Sun, Yunhan; Wang, Xiaoning; Jia, Qingxiu; Yang, Jian
Abstract: In this paper, lanthanum oxide was modified by silane coupling agent (KH560), titanate coupler NDZ-201 and dopamine hydrochloride (DP). The microstructure and chemical structure of modified La2 O3 were characterized by scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS), and the dispersion of modified lanthanum oxide in polypropylene (PP) was investigated. The results show that the three modifiers can improve the organic properties of lanthanum oxide, and the interfacial compatibility between dopamine modified La2 O3 and PP is better than the other two modifiers.